2016
DOI: 10.1111/cei.12826
|View full text |Cite
|
Sign up to set email alerts
|

H-ferritin and CD68+/H-ferritin+ monocytes/macrophages are increased in the skin of adult-onset Still's disease patients and correlate with the multi-visceral involvement of the disease

Abstract: Adult-onset Still's disease (AOSD) patients may show an evanescent salmon-pink erythema appearing during febrile attacks and reducing without fever. Some patients may experience this eruption for many weeks. During AOSD, exceptionally high serum levels of ferritin may be observed; it is an iron storage protein composed of 24 subunits, heavy (H) subunits and light (L) subunits. The ferritin enriched in L subunits (L-ferritin) and the ferritin enriched in H subunits (H-ferritin) may be observed in different tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 40 publications
1
24
1
2
Order By: Relevance
“…Our results showed that FeH was more represented than FeL in BM biopsies of patients with AOSD and MAS, as previously reported in affected tissues 18,19,23,24 . Conversely, in sera of these patients, FeL was the predominant form, as reported by LC-MS/MS.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that FeH was more represented than FeL in BM biopsies of patients with AOSD and MAS, as previously reported in affected tissues 18,19,23,24 . Conversely, in sera of these patients, FeL was the predominant form, as reported by LC-MS/MS.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first study devoted to investigating the clinical characteristics at the time of diagnosis that may be considered predictive for MAS occurrence, and to understanding whether this complication may be associated with a decreased survival rate, in one of the largest cohorts of patients with AOSD described in literature. The clinical features of our patients did not significantly differ from other available series already published, concerning the prevalence of fever, arthritis, and rash [29][30][31][32][33][34][35][36][37] . Our patients also showed high levels of inflammatory markers, as well as of serum ferritin, thus confirming the systemic inflammatory features of the disease 29,30,31,32 .…”
Section: Discussioncontrasting
confidence: 48%
“…To date, H-ferritin and CD68 1 /H-ferritin 1 cells were correlated significantly with haematological involvement, serum ferritin and CRP of our MAS patients. These results suggest potentially new biomarkers evaluating severity of the MAS clinical picture, possibly improving outcome in these patients [37,38]. In fact, diagnosis and appropriate treatments may be delayed, due to non-specific findings in the early phases of disease, thus new biomarkers may improve the management of this life-threating syndrome [39][40][41][42].…”
Section: Discussionmentioning
confidence: 98%